Inflectional Morphological Errors in EFL Academic Writing: An Error Analysis of Indonesian University Students - Wilna Tri Rahayu Wahid; Siska Bochari; Mukrim; Hastini (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Errors in inflectional morphology remain a persistent challenge in EFL learners’ writing, particularly in Indonesian contexts where in-depth analyses of error patterns and their underlying causes are still limited. This study aims to identify the types of inflectional morphological errors produced by English students at Tadulako University and to examine the factors contributing to these errors. Adopting a descriptive qualitative design, this study involved 20 fifth-semester students from the English Education Study Program. Data were collected through document analysis of students’ written assignments and semi-structured interviews with five selected participants. The data were analyzed using systematic error analysis procedures, including error identification, classification into inflectional categories, explanation of error sources, and frequency analysis. The findings indicate that verb inflection errors are the most prevalent, particularly in tenses marking and subject–verb agreement, followed by errors in plural and possessive forms. These errors are primarily attributed to first language interference, insufficient grammatical knowledge, and limited exposure to accurate language use in writing practice. This study contributes to EFL pedagogy by providing a more nuanced understanding of learners’ difficulties in using inflectional morphology and underscores the importance of integrating explicit grammar instruction with meaningful writing practice to enhance grammatical accuracy.